A Case Study on Evaluating Regional Development-Oriented Universities’ Contribution to Society Activities in Turkey - Aslı Günay (Üniversite Araştırmaları Dergisi)
This study aims to evaluate the efficiency and performance of contribution to society activities of Turkish public universities titled as regional development-oriented universities in the content of Mission Differentiation and Specialization on the Basis of Regional Development Project. Data Envelopment Analysis was applied to assess the relative contribution to society efficiency of these universities for 2018 and 2019. The results indicate that relatively efficient universities were only three and two out of fifteen universities according to their use of human and financial inputs in 2018 and 2019, respectively. Also, the overall mean score of universities is less than 0.5; hence, in total, universities were inefficient regarding their contribution to society activities in both years. Besides, the number of universities that had a 100% or higher fulfillment rate of the objectives pertaining the social contribution activities in the university’s strategic plan varied between four and seven. Although the main aim of regional development-oriented universities is to contribute to their regions’ socio-economic development, the findings show that selected universities have a poor performance in contributing to society activities, in other words, partly in third mission activities.